1996
DOI: 10.1007/bf00837624
|View full text |Cite
|
Sign up to set email alerts
|

Single-photon emission tomographic quantification in spherical objects: effects of object size and background

Abstract: A method was set up for single-photon emission tomographic (SPET) quantification of radioactivity concentration in small anatomical structures. The method is based on the theoretical model proposed by Kessler et al. (J. Comput Assist Tomogr 1984; 8: 514-522) describing the effects of spatial resolution (partial volume effect and spillover) on the quantification of radioactivity concentration in small spherical objects. The model was validated here in SPET, by phantom experimental measurements, in relation to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…The RC depends not only on tumor volume but also on image sampling. The RC can be calculated by assuming no surrounding activity, and the uptake surrounding the tumor, which has to be estimated to compensate for spilling in, can be accounted for subsequently by use of a simple formula when the RC is applied (17)(18)(19)(20)(21).…”
Section: Correction Methods Applied At Regional Levelmentioning
confidence: 99%
“…The RC depends not only on tumor volume but also on image sampling. The RC can be calculated by assuming no surrounding activity, and the uptake surrounding the tumor, which has to be estimated to compensate for spilling in, can be accounted for subsequently by use of a simple formula when the RC is applied (17)(18)(19)(20)(21).…”
Section: Correction Methods Applied At Regional Levelmentioning
confidence: 99%
“…However, studies addressing the magnitude of the problem in SPET activity quantification are limited, particularly with respect to object shape and nontarget activity. In addition to the work by our group with 131 I [5,6], there have been two recent studies on effects of object size on technetium-99m quantification and the use of recovery coefficients (RCs) in SPET [7,8]. In these two studies the partial volume correction models proposed by Hoffman et al [9] and Kessler et al [10] for position emmission tomography (PET) were assessed for SPET quantification of spherical objects.…”
Section: Introductionmentioning
confidence: 99%
“…Hot spot RCs (to correct for spill-out) and cold spot RCs (to correct for spill-in) were determined in calibration experiments using spheres of different sizes. Zito et al used these RCs to correct measured radioactivity concentrations in spheres for a range of object sizes and showed good agreement with the true radioactivity concentration [8]. On the other hand the work of Geworski et al demonstrated that while partial volume correction based on physical phantom studies is feasible in PET, it is subject to serious difficulties in the case of SPET [7].…”
Section: Introductionmentioning
confidence: 99%
“…Countbased methods [12,13,29,30] use only the maximum of the profile. They are very susceptible to background noise, and applying the recovery coefficient correction was cumbersome [12,13,31]. Geometry-based methods attempted to locate the endo-and epicardial borders by edge detection using the first [9] or second derivative [32], thresholding [1] or deconvolution [33].…”
Section: Discussionmentioning
confidence: 99%